Sekularyzacja, laicyzacja, globalizacja, cyfrowość - Anglarès, Michel (Studia Pastoralne, 2020)
The emergence of new sciences and technologies is contributing to profound changes in all communities of the world. Terms such as secularisation, mondialisation (globalisation) and digitalisation express man’s new reference to nature, other men, himself, and the religious sphere. Christianity should look for new approaches to the evangelical way of life in this new world. In view of the fact that the human world contains both positive and negative elements, Christians should strive to discern these contemporary changes of humankind. On the one hand, this world, still in the process of creation, is loved unconditionally by God: For God so loved the world that he gave his only Son (John 3:16). Therefore, Christ’s disciples should also love this world instead of showing fear of it. On the other hand, the Holy Spirit speaks to us through all the events of our lives, including those that are influencing the current changes within our societies. This is why it is necessary to discern His presence and inspirations.